Topology of stratified spaces: [... based on lectures given at the Workshop on the Topology of Stratified Spaces that was held at the Mathematical Sciences Research Institute in Berkeley, CA, from September 8 to September 12, 2008] - Friedman, Greg; Hunsicker, Eugénie; Libgober, Anatoly; Maxim, Laurenţiu G. (Mathematical Sciences Research Institute publications, 2011)
"Appearance of singularities is pervasive in many problems in topology, differential geometry, and algebraic geometry. This book concerns the study of singular spaces using techniques from a variety of areas of geometry and topology and the interactions among them. Expository chapters by well-known experts cover intersection homology, L2 cohomology and differential operators, topology of algebraic varieties, signatures and characteristic classes, mixed Hodge theory, and elliptic genera of singular complex and real algebraic varieties. The book concludes with a list of open problems"--Provided by publisher
Includes bibliographical references and index
Keywords: Konferenzschrift